Connotation of Migrant in Modern Migrants’ Literature - Elena Grudeva (Journal of History Culture and Art Research, 2022)
The issues of the relationship between language and culture are becoming increasingly important in connection with the processes of globalization, increasing migration flows, the expansion of international contacts, and the aggravation of interethnic conflicts. The study of the works of migration literature provides access to the cognitive structures of thinking and the worldview of the migrant author, which determine the specifics of his penetration into other linguistic cultures. The peculiarities of the migrant's interaction with the new cultural environment, the identification of his behavior patterns taking into account differences in national mentalities, his assimilation in society with other stereotypes of thinking and value orientations are of interest to researchers. Also, the intercultural specificity of the migrant image needs a more thorough study, since this specificity is due to the intersection of two linguistic pictures of the world in the perception of one person. The work is an analysis of the lingua-cultural image of migrant in modern migration literature - the novels by American writers M. Schrayer and J. Kwok. Semantic field migrant was modeled on the basis of some typical characteristics. The image of a migrant acts as a conceptual center in the novels, combining contexts with cultural labeling, the presence of several variants of meaning and author’s connotative shades. Lexical units were selected from the novels by continuous sampling. The analysis of 110 dictionary units allowed us to conclude that the “migrant” acts as the core of the lexical and semantic field, i.e. a lexeme with a generalizing, integral meaning. The analysis of language means showed also the content of the image of a migrant. The composition of the lexical and semantic field, as well as the nearest lexical environment, reveal a certain inconsistency inherent in the author’s image of a migrant.